Stationary co-operating of acoustic radiation is with circular plate - Лозовик, Тамара Миколаївна (Eastern-European Journal of Enterprise Technologies, 2011)
The stationary co-operating of wave of surplus pressure of audio-frequency is analysed with a round izotropic plate. The calculation model of the phenomenon is built on the basis of radial acoustics